Socioemotional wealth and decline in a family-owned firm: A study of the Guerra S.A. - Buchweitz, Michele Josiane Rutz (2019)
This study sought to identify the factors that led the company Guerra S.A. to the decline and subsequent closure of the activities. Accurate information provided by accounting enables assertive decisions over the life of organizations, making them competitive and fostering development over the generations of family business owners. Thus, this research was developed from the perspective of evolutionary cycles and social-emotional richness, focusing in particular on organizational decline—a phase of the life cycle model proposed by Miller and Friesen (1984). The research was carried out through content analysis of articles extracted from newspapers and other virtual media. We opted for a qualitative approach, when using data obtained from written sources. The evidence obtained suggests that the decline, the last phase of the organizational life cycle and, consequently, the bankruptcy and closure of the activities of Guerra S.A. was due to the fact that decision-makers do not act effectively and energetically in solving problems faced by the company and by disputes of interest between the parent company and the family member that was responsible for minority shares. In summary, this research helps family companies and their representatives understand the relevance that emotional aspects can bring to the family business through the socio-emotional richness approach.